Chewing Habits Among Rural Women In Pondicherry - Jagadeesan M; Rotti S.B; Danabalan M; Narayan K.A (Wolters Kluwer Medknow Publications, 1997)
Research question: 1. What is the prevalence of chewing habits among rural women? 2. What are the factors associated with their use? Objectives: To find out the prevalence of chewing habits and correlates of chewing habits. Design: Cross- sectional descriptive study. Participants: Females aged 15 years and above. Study variables: Age, educational status, marital status, occupation, income, type of family, age of starting habitual chewing persons influencing chewing habits and reasons for continuing the habit. Outcome variable : Chewing habits. Statistical analysis: Chi- square test, Analysis of variance. Odds ratio and Logistic regression. Results: The prevalence of chewing betel quid was 24.6% betel quid with tobacco 13.7% and betel nut 0.2%. Mean age of starting betel quid was 22.7 years and betel quid with tobacco, 16.5 years. Friends were the most influencing persons of starting the habit. The most common reasons for continuing were craving for the substances. There was direct relationship of chewing habits with age and inverse relationship with educational status. The chewing habits were more prevalent among married women and women engaged as agricultural labourers. Conclusion: Chewing betel quid with or without tobacco is a common practice among rural women. It is influenced by socio- cultural factors.